Crop intensification in red soils predominated rainfed upland rice monocrop areas - Singh, C. V.; Maiti, D. (Indian Farming, 2018)
In a systematic study on upland rice-based cropping systems, different cropping systems were agroeconomically assessed for their performance. It was inferred that upland rice intercropped with pigeonpea was the best system for rainfed red sandy loam soils. From the gross returns view, rice cv. intercropped with groundnut appeared to be the next best system, though higher cost of cultivation involved with groundnut cultivation placed it on 3rd rank. On the other hand, rice intercropped with finger millet stood on second place as cost of cultivation was less in former than later. It was noted that in the given soils, intercropping out yielded other cropping systems. Relay or sequence cropping of rabi crops proved economically unviable when compared with rice + pigeonpea intercropping under red sandy loam soils even if relay or sequence crop established in the presence of optimum moisture at sowing. As the response of rice varieties varied with rainfall pattern during the cropping season, varietal mixtures of rice cultivars intercropped with pigeonpea in 2:2:1 row ratio proved better than single rice cultivar intercropped with pigeonpea. Farmers usually broadcast upland rice and show their reluctance for sowing rice behind the plough in furrows. To overcome this problem studies were conducted involving different methods of sowings and it was observed that broadcast of rice seed @100 kg/ha in the interspace of 75 cm between two rows of pigeonpea was as good as row seeding of both crop in 4:1 row ratio.